2009
DOI: 10.1002/stem.62
|View full text |Cite
|
Sign up to set email alerts
|

Human Fetal Auditory Stem Cells Can Be Expanded In Vitro and Differentiate Into Functional Auditory Neurons and Hair Cell-Like Cells

Abstract: In the quest to develop the tools necessary for a cell-based therapy for deafness, a critical step is to identify a suitable stem cell population. Moreover, the lack of a self-renovating model system for the study of cell fate determination in the human cochlea has impaired our understanding of the molecular events involved in normal human auditory development. We describe here the identification and isolation of a population of SOX21OCT41 human auditory stem cells from 9-week-old to 11-week-old fetal cochleae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 39 publications
3
57
0
Order By: Relevance
“…Of these studies, two have reported the use of human stem cells for auditory neuron replacement [11,12], and this will eventually be critical for translation of this therapy into clinical practice. In developing a cell replacement therapy for hearing loss, donor stem/progenitor cells must also be electrically active and capable of organized outgrowth of processes, including forming synapses on appropriate cells/tissues in the peripheral and central auditory system [13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, two have reported the use of human stem cells for auditory neuron replacement [11,12], and this will eventually be critical for translation of this therapy into clinical practice. In developing a cell replacement therapy for hearing loss, donor stem/progenitor cells must also be electrically active and capable of organized outgrowth of processes, including forming synapses on appropriate cells/tissues in the peripheral and central auditory system [13,14].…”
mentioning
confidence: 99%
“…Several laboratories have now explored the possibility of using stem cells to replace auditory neurons, which progressively degenerate after hearing loss [3][4][5][6][7][8][9][10][11][12]. Of these studies, two have reported the use of human stem cells for auditory neuron replacement [11,12], and this will eventually be critical for translation of this therapy into clinical practice.…”
mentioning
confidence: 99%
“…To increase cell proliferation, growth factors were being used. Growth factors such as EGF, IGF, BFGF, and N-2® and B-27® supplements (Gibco) were used and reported to enhance the growth of these cells [18,26] . Auditory cells cultured with the supplementation of the growth factors EGF, IGF, BFGF, and N-2® and B-27® supplements in this study showed a significantly higher proliferation rate than cells without the supplementation of additional growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Three types of stem cells have been successfully differentiated into cell types that can be transplanted to improve SNHL: embryonic stem cells, adult inner ear stem cells, and neuronal stem cells. 84 Transplant of these cells presents a unique problem given the accessibility and size of the structures involved as well as the complicated relationship between cell types. Injection approaches are similar to those used for gene therapy and include round window, 85 lateral semicircular canal, 86 posterior semicircular canal, 87 cochlear lateral wall, 86,88 internal auditory meatus, 89 and modiolus.…”
Section: Stem Cell Therapy For Sensorineural Hearing Lossmentioning
confidence: 99%